Potensi Bencana Tsunami dan Kesiapsiagaan Masyarakat Menghadapi Bencana Studi Kasus Desa Sumberagung Banyuwangi Jawa Timur - S Sunarto; Muh. Aris Marfai (Forum Geografi, 2012)
This research aims to, 1) identify the physical condition and vulnerability due to tsunami at Pancer, Sumberagung Banyuwangi and 2) identify the awareness program done by community to reduce the risk and impact due to tsunami. Field observation and analysis of morphology, topography and physical characteristic of the coastal area of Pancer has been done in this research. Interview with key person and stakeholders has been conducted in order to understand the awareness system and program done by the community. Descriptive analysis has been used to describe the research result. From the topographical point of view, study area consist of lowland and hilly area. Lowland area is dominated by settlement and paddy field, meanwhile the hilly area is mainly for forest and dry farming system. Lowland area is the most vulnerable area for inundation due to tsunami. Coastal community has knowledge on tsunami hazard. Many program has been implemented to strengthen the community capacity and awareness, such as campaign, workshop for evacuation route identification, and evacuation simulation.